Coated modified positive electrode material and preparation method thereof, positive electrode plate, lithium ion battery and electric device
By coating hydrotalcite-type two-dimensional layered materials on lithium nickel-cobalt manganate material to form a bimetal oxide layer, the problem of poor rate performance of single-crystal positive electrode material is solved, and the rate performance and cycle stability of lithium-ion batteries are improved , enhancing high-temperature storage performance.
Patent Information
- Application Number
- CN202411344423.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-10
AI Technical Summary
The poor rate performance of single-crystal positive electrode materials in lithium-ion batteries leads to deterioration of life and safety performance, and there are insufficient structural stability and high temperature resistance compared with polycrystal positive electrode materials.
Using coated modified positive electrode material, by combining nickel-cobalt lithium manganate with hydrotalcite two-dimensional layered material, bimetal oxide cladding layer is formed, which enhances electron conductivity and improves interface stability and reduces lithium ions. migration barrier.
It significantly improves the rate performance, cycle stability and high-temperature storage performance of the positive electrode material, reduces side reactions and transition metal dissolution, and improves the overall performance of the battery.
Smart Images

Figure CN119297229A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a coated and modified positive electrode material and a preparation method thereof, a positive electrode sheet, a lithium-ion battery and an electrical device. Background Art
[0002] With the rapid development of the new energy industry, lithium-ion batteries have attracted much attention due to their high energy density and low maintenance costs. Lithium-ion batteries are a type of battery composed of a positive electrode, a negative electrode, and a non-aqueous electrolyte solution. Among them, the performance of the positive electrode material has a crucial impact on the performance of lithium-ion batteries, such as rate, energy density, and service life. Nickel cobalt manganese oxide materials have become a research hotspot in recent years due to their advantages such as high reversible capacity and fast charging and discharging. Nickel cobalt manganese oxide materials include single crystal positive electrode materials and polycrystalline positive electrode materials. The energy density of polycrystalline positive electrode materials is relatively high, but when participating in the charge-discharge of lithium-ion batteries, the electrolyte easily enters the interior of the particles to cause side reactions, and transition metal dissolution occurs at the same time, resulting in deterioration of life and safety performance.
[0003] Compared with polycrystalline cathode materials, single crystal cathode materials have better structural stability and high temperature resistance. However, compared with polycrystalline cathode materials, single crystal cathode materials have poor rate performance. Summary of the invention
[0004] Based on this, the present application provides a coated modified positive electrode material and a preparation method thereof, a positive electrode plate, a lithium ion battery and an electrical device to improve the rate performance of the positive electrode material.
[0005] The first aspect of the present application provides a coated modified positive electrode material, comprising:
[0006] A substrate, wherein the substrate comprises a nickel cobalt lithium manganese oxide material, wherein the nickel cobalt lithium manganese oxide material comprises a doping element, and the doping element comprises one or more of Sr, Ga, In, Ta, W, Zr, B, Al, Sb, Mo, Ti, La, Na and Sn; and
[0007] A coating layer is coated on at least a portion of the surface of the substrate, wherein the coating layer comprises a bimetallic oxide, wherein the bimetallic oxide comprises an M element and a Q element, wherein the M element comprises one or more elements selected from the group consisting of Mg, Zn, Ni, Co, Cu, Ca, Fe, Be, Ba, Sr and Mn, and the Q element comprises one or more elements selected from the group consisting of Al, Cr, Co, Fe, Sc, Ga, In and V.
[0008] In some embodiments, the positive electrode material has at least one of the following features (1)-(6):
[0009] (1) The chemical formula of the bimetallic oxide is M m Qq O n , where 1 ≤ m < 8, 1 ≤ q < 4, 1 ≤ n ≤ 5;
[0010] (2) The mass of the double metal oxide accounts for 0.3% - 3% of the mass of the lithium nickel cobalt manganese oxide material;
[0011] (3) The double metal oxide is coated on at least a part of the surface of the lithium nickel cobalt manganese oxide material;
[0012] (4) The chemical formula of the lithium nickel cobalt manganese oxide material is Li a Ni x Co y Mn z A b O2, 1 ≤ a ≤ 1.1, 0.5 ≤ x ≤ 1, 0 < y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z + b = 1, 0 < b ≤ 0.02, and the A element includes one or more of Ga, In, Ta, W, Zr, B, Al, Sb, Mo, Ti, La, Na, Sr, and Sn;
[0013] (5) The volume average particle size Dv50 of the positive electrode material is 2.5 μm - 5.5 μm;
[0014] (6) The matrix includes single crystal particles and / or polycrystalline particles.
[0015] The second aspect of the present application provides a method for preparing a coated and modified positive electrode material, including the following steps:
[0016] Roast a mixture containing a matrix and a hydrotalcite-like two-dimensional layered material to prepare the positive electrode material; where the matrix contains a lithium nickel cobalt manganese oxide material, the lithium nickel cobalt manganese oxide material contains doping elements, and the doping elements include one or more of Sr, Ga, In, Ta, W, Zr, B, Al, Sb, Mo, Ti, La, Na, and Sn; the chemical formula of the hydrotalcite-like two-dimensional layered material is [M 2+ 1-m Q 3+ m (OH)2] q+ (X n- ) q / n .yH2O, 0.17 ≤ m ≤ 0.35, 1 ≤ n ≤ 4, 2 ≤ q ≤ 6, 1 ≤ y ≤ 5, and the M 2+ ion is Mg 2+ 、Zn 2+ 、Ni 2+ 、Co 2+ 、Cu 2+ 、Ca 2+ 、Fe 2+ 、Be2+ , Ba 2+ , Sr 2+ and Mn 2+ One or more of Q 3+ Ion is A1 3+ Cr 3+ 、Co 3+ , Fe 3+ Sc 3+ , Ga 3+ 、In 3+ and V 3+ One or more of X n- Ion is CO3 2- 、NO3 - 、F - , Cl - Br - ,I - 、CrO4 2 -H2PO4 - PO4 3- 、SO4 2- and SO3 2- One or more of;
[0017] The positive electrode material includes a substrate and a coating layer coated on at least a portion of the surface of the substrate, the substrate includes a nickel cobalt manganese oxide material, the coating layer includes a bimetallic oxide, the bimetallic oxide includes an M element and a Q element, the M element includes one or more elements of Mg, Zn, Ni, Co, Cu, Ca, Fe, Be, Ba, Sr and Mn, and the Q element includes one or more elements of Al, Cr, Co, Fe, Sc, Ga, In and V.
[0018] In some embodiments, the mass of the hydrotalcite-like two-dimensional layered material accounts for 0.3%-3% of the mass of the lithium nickel cobalt manganese oxide material contained in the matrix; and / or the calcination temperature is 500°C-800°C, the time is 8h-12h, and the calcination atmosphere includes nitrogen.
[0019] In some embodiments, the method for preparing the hydrotalcite-like two-dimensional layered material comprises:
[0020] will contain the M 2+ ions and the Q 3+ A mixed salt solution containing the X n- After mixing with the alkaline solution of ions, the crystal nucleus grows to prepare the hydrotalcite-like two-dimensional layered material;
[0021] Optionally, the nucleation temperature of the crystal nucleus growth is 80°C-120°C;
[0022] Optionally, the concentration of the alkali solution is 0.1 mol / L - 2 mol / L.
[0023] In some embodiments, the chemical formula of the lithium nickel cobalt manganese oxide material is Li a Ni x Co y Mn z A b O2, where 1 ≤ a ≤ 1.1, 0.5 ≤ x ≤ 1, 0 < y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z + b = 1, 0 < b ≤ 0.02, and the A element includes one or more of Ga, In, Ta, Sr, W, Zr, B, Al, Sb, Mo, Ti, La, Na, and Sn.
[0024] In some embodiments, the preparation method of the matrix includes:
[0025] Mixing a lithium nickel cobalt manganese oxide material precursor, a lithium source, and an additive containing the A element, and then performing a sintering treatment;
[0026] Optionally, the chemical formula of the lithium nickel cobalt manganese oxide material precursor is Ni x Co y Mn z (OH)2, where 0.5 ≤ x ≤ 1, 0 < y ≤ 0.3, 0 < z ≤ 0.3;
[0027] Optionally, the lithium source includes one or more of LiOH, Li2CO3, Li2SO4, LiCl, and LiNO3;
[0028] Optionally, the additive includes one or more of an oxide, hydroxide, chloride, sulfate, and nitrate containing the A element;
[0029] Optionally, the sintering treatment includes a first sintering stage and a second sintering stage;
[0030] Optionally, the sintering temperature of the first sintering stage is 940°C - 970°C, the sintering time is 8 h - 13 h, and the sintering atmosphere includes one or both of oxygen and air;
[0031] Optionally, the sintering temperature of the second sintering stage is 400°C - 500°C, and the sintering time is 5 h - 8 h.
[0032] The third aspect of the present application provides a positive electrode sheet, including the coated and modified positive electrode material of the first aspect of the present application or the coated and modified positive electrode material prepared by the preparation method of the second aspect of the present application.
[0033] The fourth aspect of the present application provides a lithium ion battery, including the positive electrode sheet of the third aspect of the present application.
[0034] The fifth aspect of the present application provides an electrical device, comprising the lithium-ion battery of the fourth aspect of the present application.
[0035] In the above-mentioned coated modified positive electrode material, the high-valent cationic metal with a larger ion radius doped in the nickel-cobalt-manganese oxide lithium material can enter the lattice of the matrix, increase the distance between the lithium layer and the oxygen layer, reduce the migration barrier of lithium ions, and accelerate the transmission of lithium ions. At the same time, the bimetallic oxide in the coating layer has a high electrochemical activity, which can further enhance the electronic conductivity of the positive electrode material and greatly improve the rate performance of the positive electrode material; and the bimetallic oxide can also increase the interface stability between the positive electrode material and the electrolyte, reduce side reactions, lattice oxygen precipitation and transition metal dissolution, thereby improving the rate performance, cycle stability and high-temperature storage performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions in the embodiments of the present application and to more completely understand the present application and its beneficial effects, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.
[0037] Figure 1 This is a scanning electron microscope image (SEM image) of the positive electrode material prepared in Example 1.
[0038] Figure 2 The EIS impedance diagrams of the positive electrode material prepared in Example 1 and Comparative Example 1 after cycling. DETAILED DESCRIPTION
[0039] For ease of understanding of the present invention, the application will be described more fully below with reference to relevant embodiments. The following provides preferred embodiments of the application. However, the application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the application more thorough and comprehensive.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0041] The terms "and / or", "or / and", and "and / or" used herein include any one of two or more related listed items, and also include any and all combinations of the related listed items, wherein the any and all combinations include any combination of two related listed items, any more related listed items, or all related listed items. It should be noted that when at least three items are connected by at least two conjunctions selected from "and / or", "or / and", and "and / or", it should be understood that in the present application, the technical solution undoubtedly includes technical solutions connected by "logical and", and also undoubtedly includes technical solutions connected by "logical or".
[0042] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0043] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0044] Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.
[0045] The temperature parameters in this application, unless otherwise specified, allow both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.
[0046] In this application, unless otherwise specified, the size, particle size, and diameter generally refer to the average value. In this application, "particle size" and "particle size" have the same definition, both representing the average particle size of a sphere or a spheroid.
[0047] Herein, the “suitable” mentioned in “suitable combination”, “suitable method”, “any suitable method”, etc., shall be based on the ability to implement the technical solution of this application, solve the technical problems of this application, and achieve the expected technical effects of this application.
[0048] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.
[0049] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.
[0050] In the description of the application, "plurality" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0051] If there is no special description, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. If there is no special description, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0052] If there is no special explanation, all the steps of the present application can be performed sequentially or randomly, preferably sequentially.
[0053] Nickel cobalt manganese oxide materials have become a research hotspot in recent years due to their high reversible capacity and fast charge and discharge. Nickel cobalt manganese oxide materials include single crystal positive electrode materials and polycrystalline positive electrode materials. Polycrystalline positive electrode materials have a high energy density, but there are a large number of grain boundaries and poor structural stability. When participating in the charge and discharge of lithium-ion batteries, the anisotropic expansion and contraction of the material can easily cause obvious cracking and differentiation in the polycrystalline positive electrode material. The electrolyte can easily enter the interior of the particles to cause side reactions, and transition metals are dissolved, resulting in deterioration of life and safety performance. Compared with polycrystalline positive electrode materials, single crystal positive electrode materials have no grain boundaries inside, which can effectively deal with the poor performance caused by grain boundary crushing and the resulting poor performance, and have better structural stability and high temperature resistance. However, compared with polycrystalline positive electrode materials, single crystal positive electrode materials have the problem of poor rate performance.
[0054] Based on the above problems, the present application adopts hydrotalcite-like two-dimensional layered materials to coat nickel cobalt manganese oxide materials, and utilizes the high electrochemical activity of hydrotalcite-like two-dimensional layered materials and the adjustable denaturation of metal cation layers and interlayer anions to enhance the electronic conductivity of the positive electrode material, reduce the interfacial impedance, and improve the rate performance and thermal stability of the positive electrode material, thereby forming a composite positive electrode material with good conductivity, high rate performance, high energy density and strong stability.
[0055] One or more embodiments of the present application provide a coated modified positive electrode material, including a substrate and a coating layer coated on at least a portion of the surface of the substrate; the substrate includes a nickel cobalt manganese oxide material, the nickel cobalt manganese oxide material includes doping elements, and the doping elements include one or more of Sr, Ga, In, Ta, W, Zr, B, Al, Sb, Mo, Ti, La, Na and Sn; the coating layer includes a bimetallic oxide, the bimetallic oxide includes an M element and a Q element, the M element includes one or more of Mg, Zn, Ni, Co, Cu, Ca, Fe, Be, Ba, Sr and Mn, and the Q element includes one or more of Al, Cr, Co, Fe, Sc, Ga, In and V.
[0056] It can be understood that in the above-mentioned coated modified positive electrode material, the high-valent cationic metal with a larger ion radius doped in the nickel cobalt manganese oxide material can enter the lattice of the matrix, increase the distance between the lithium layer and the oxygen layer, reduce the migration barrier of lithium ions, and accelerate the transmission of lithium ions. At the same time, the bimetallic oxide in the coating layer has a high electrochemical activity, which can further enhance the electronic conductivity of the positive electrode material, and greatly improve the rate performance of the positive electrode material; and the bimetallic oxide can also increase the interface stability between the positive electrode material and the electrolyte, reduce side reactions, lattice oxygen precipitation and transition metal dissolution, thereby improving the rate performance, cycle stability and high-temperature storage performance of the positive electrode material.
[0057] It should be noted that the "lithium nickel cobalt manganese oxide material" in the context is not limited to LiNiMnCoO2. As long as it is an oxide containing lithium, nickel, manganese and cobalt elements, for example, oxides containing lithium, nickel, manganese and cobalt elements doped with other metal elements (such as one or more of Sr, Ga, In, Ta, W, Zr, B, Al, Sb, Mo, Ti, La, Na and Sn) are all within the scope of protection of this application.
[0058] It can be understood that the technical solution of the present application does not exclude the situation where the substrate and / or coating layer further includes other materials, especially the situation where the substrate further includes other positive electrode active materials and / or the coating layer further includes other coating materials.
[0059] In some embodiments, the substrate mainly includes or contains only lithium nickel cobalt manganese oxide material, and the coating layer mainly includes or contains only a bimetallic oxide containing M elements (M elements include one or more elements of Mg, Zn, Ni, Co, Cu, Ca, Fe, Be, Ba, Sr and Mn) and Q elements (Q elements include one or more elements of Al, Cr, Co, Fe, Sc, Ga, In and V).
[0060] In some embodiments, the bimetallic oxide of the coating layer is directly coated on at least a portion of the surface of the lithium nickel cobalt manganese oxide material of the substrate.
[0061] It is understood that the matrix and / or coating layer may further include other materials, but the content thereof should not be such that it becomes the main component, so as to avoid affecting the coating of the bimetallic oxide on the lithium nickel cobalt manganese oxide material.
[0062] In some embodiments, the chemical formula of the bimetallic oxide is M m Q q O n , where 1≤m<8, 1≤q<4, 1≤n≤5.
[0063] In some embodiments, the mass of the bimetallic oxide accounts for 0.3%-3% of the mass of the lithium nickel cobalt manganese oxide material contained in the matrix; for example, it can be but not limited to 0.3%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, or the range between any two of the above values. Thus, the high electrochemical activity of the bimetallic oxide is utilized to further enhance the electronic conductivity of the positive electrode material, and greatly improve the rate performance of the positive electrode material.
[0064] As a possible implementation, the bimetallic oxide is coated on at least a portion of the surface of the lithium nickel cobalt manganese oxide material.
[0065] In some embodiments, the chemical formula of the lithium nickel cobalt manganese oxide material is Li a Ni x Co y Mn z A bO2, where 1 ≤ a ≤ 1.1, 0.5 ≤ x ≤ 1, 0 < y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z + b = 1, 0 < b ≤ 0.02. The A element includes one or more of Ga, In, Ta, W, Zr, B, Al, Sb, Mo, Ti, La, Na, Sr, and Sn. Thus, by doping high-valence metal cations with large ionic radii into the lattice of the lithium nickel cobalt manganese oxide material, the crystal growth direction of the lithium nickel cobalt manganese oxide material can be affected, resulting in grain refinement. The harmful stress caused by the lattice contraction during the H2-H3 phase transition can be eliminated by fracture toughening, and the local component inhomogeneity of the material can be eliminated, enhancing the structural stability. At the same time, the spacing between the lithium layer and the oxygen layer can be increased, the migration barrier of lithium ions can be reduced, the transmission of lithium ions can be accelerated, and the rate performance of the material can be further improved.
[0066] It should be noted that by simultaneously doping high-valence metal cations with large ionic radii into the lattice of the lithium nickel cobalt manganese oxide material and forming a coating layer containing double metal oxides on the surface of the lithium nickel cobalt manganese oxide material, it is beneficial to stabilize the bulk structure of the cathode material during lithium deintercalation and insertion and the interface stability with the electrolyte, reduce side reactions, lattice oxygen precipitation, and transition metal dissolution, improve the cycle stability, high-temperature storage performance, and rate performance of the cathode material, and it is not easy to be difficult to exert the above effects due to too little doping amount, nor is it easy to affect the capacity of the battery and cause a decline in the electrochemical performance of the battery due to too high doping amount. The cathode material can still maintain good performance at a high rate of 4C.
[0067] In some embodiments, the volume average particle size Dv50 of the cathode material is 2.5 μm - 5.5 μm; for example, it can be, but is not limited to, 2.5 μm, 2.6 μm, 2.8 μm, 3 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 4 μm, 4.2 μm, 4.4 μm, 4.6 μm, 4.8 μm, 5 μm, or the range between any two of the above values, etc.
[0068] As a possible embodiment, the matrix includes single crystal particles and / or polycrystalline particles.
[0069] One or more embodiments of the present application provide a method for preparing a coated and modified cathode material, which can be used to prepare the above-mentioned coated and modified cathode material. The preparation method includes the following steps:
[0070] Roast a mixture containing a matrix and a hydrotalcite-like two-dimensional layered material to prepare the cathode material; wherein, the matrix contains a lithium nickel cobalt manganese oxide material, the lithium nickel cobalt manganese oxide material contains doping elements, and the doping elements include one or more of Sr, Ga, In, Ta, W, Zr, B, Al, Sb, Mo, Ti, La, Na, and Sn; the chemical formula of the hydrotalcite-like two-dimensional layered material is [M 2 +1-m Q 3+ m (OH)2] q+ (X n- ) q / n .yH2O, 0.17≤m≤0.35, 1≤n≤4, 2≤q≤6, 1≤y≤5, M 2+ Ion is Mg 2+ 、Zn 2+ 、Ni 2+ 、Co 2+ , Cu 2+ , Ca 2+ , Fe 2+ 、Be 2+ , Ba 2+ , Sr 2+ and Mn 2+ One or more of Q 3+ Ion is A1 3+ Cr 3+ 、Co 3+ , Fe 3+ Sc 3+ , Ga 3+ 、In 3+ and V 3+ One or more of X n- Ion is CO3 2- 、NO3 - 、F - , Cl - Br - ,I - 、CrO4 2 -H2PO4 - PO4 3- 、SO4 2- and SO3 2- One or more of;
[0071] The positive electrode material includes a substrate and a coating layer coated on at least a portion of the surface of the substrate, the substrate includes a nickel cobalt manganese oxide material, the coating layer includes a bimetallic oxide, the bimetallic oxide includes an M element and a Q element, the M element includes one or more elements of Mg, Zn, Ni, Co, Cu, Ca, Fe, Be, Ba, Sr and Mn, and the Q element includes one or more elements of Al, Cr, Co, Fe, Sc, Ga, In and V.
[0072] After high-temperature sintering, the hydrotalcite-like two-dimensional layered material undergoes a structural topological transformation into a layered bimetallic oxide with the general chemical formula M m Q q O n , where 1≤m<8, 1≤q<4, 1≤n≤5.
[0073] In the preparation method provided in the present application, a two-dimensional layered material of hydrotalcite is used to coat the lithium nickel cobalt manganese oxide material, and the two-dimensional layered material of hydrotalcite is used to have high electrochemical activity and adjustable variability of components and structures, thereby forming a composite positive electrode material with good conductivity, high rate performance, high energy density and strong stability. At the same time, the two-dimensional layered material of hydrotalcite can also increase the distance between the lithium layer and the oxygen layer, reduce the migration barrier of lithium ions, accelerate the transmission of lithium ions, and greatly improve the rate performance of the material.
[0074] In the prepared coated modified positive electrode material, the composition, structure and properties of the lithium nickel cobalt manganese oxide material in the matrix and the bimetallic oxide in the coating layer are as described above and will not be repeated in the method.
[0075] It should be noted that the "hydrotalcite-like two-dimensional layered materials" mentioned in the context refer to hydrotalcite-like layered materials containing transition metals, also known as layered double hydroxyl composite metal hydroxides (Layered Double Hydrotalcites, abbreviated as LDHs), which have the characteristics of adjustable layer cation and interlayer anion structure. After high-temperature sintering, the hydrotalcite-like two-dimensional layered materials undergo a structural topological transformation into layered double metal oxides, and the final coating layer material exists in the form of oxides.
[0076] In some embodiments, the mass of the hydrotalcite-like two-dimensional layered material accounts for 0.3%-3% of the mass of the nickel-cobalt-manganese-oxide lithium material contained in the matrix; for example, it can be but not limited to 0.3%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, or the range between any two of the above values. When the mass ratio of the nickel-cobalt-manganese-oxide lithium material to the hydrotalcite-like two-dimensional layered material is within the above range, the hydrotalcite-like two-dimensional layered material can exert a higher electrochemical activity, further enhance the electronic conductivity of the positive electrode material, and greatly improve the rate performance of the positive electrode material.
[0077] As a possible implementation manner, the calcination temperature is 500°C-800°C; for example, it can be but not limited to 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C or a range between any two of the above temperatures.
[0078] In some exemplary embodiments, the calcination time is 8 h-12 h; for example, it may be but is not limited to 8 h, 9 h, 10 h, 11 h, 12 h or a range between any two of the above times.
[0079] In some optional embodiments, the calcination atmosphere of the calcination process includes nitrogen.
[0080] It should be noted that the temperature and time of the calcination treatment can be combined in any appropriate manner, and both can be selected from any temperature and time of the calcination treatment described in this article.
[0081] When the temperature and time of the calcination treatment are respectively within the above ranges, the prepared positive electrode material has good particle consistency and dispersibility, good coating effect, and can maintain the electrochemical activity of the material to the greatest extent.
[0082] In some embodiments, the method for preparing a hydrotalcite-like two-dimensional layered material comprises: 2+ Ions and Q 3+ A mixed salt solution containing X n- After the alkaline solution of ions is mixed, crystal nucleus growth is carried out to prepare a hydrotalcite-like two-dimensional layered material.
[0083] In some optional embodiments, the nucleation temperature of the crystal nucleus growth is 80°C-120°C; for example, it can be but not limited to 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C.
[0084] As a non-limiting example, the nucleation time of the crystal nucleus growth is 22h-26h; for example, it can be but not limited to 22h, 23h, 24h, 25h, 26h or a range between any two of the above times.
[0085] In some embodiments, M 2+ Ions and Q 3+ A mixed salt solution containing X n- The steps of mixing the ionic alkaline solution include:
[0086] Will include M 2+ Ions and Q 3+ A mixed salt solution containing X n- The ionic alkaline solution was mixed at a drop rate of 1:1.
[0087] As a possible implementation, the concentration of the alkali solution is 0.1 mol / L - 2 mol / L; for example, it can be, but is not limited to, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.2 mol / L, 1.3 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.7 mol / L, 1.8 mol / L, 1.9 mol / L, 2 mol / L, or the range between any two of the above concentrations, etc.
[0088] In some embodiments, the chemical formula of the lithium nickel cobalt manganese oxide material is Li a Ni x Co y Mn z A b O2, 1 ≤ a ≤ 1.1, 0.5 ≤ x ≤ 1, 0 < y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z + b = 1, 0 < b ≤ 0.02. The A element includes one or more of Ga, In, Ta, W, Zr, B, Al, Sb, Mo, Ti, La, Na, Sr, and Sn.
[0089] In some embodiments, the method for preparing the core includes: mixing a lithium nickel cobalt manganese oxide material precursor, a lithium source, and an additive containing the A element, and then performing a sintering treatment.
[0090] In some alternative embodiments, the chemical formula of the lithium nickel cobalt manganese oxide material precursor is Ni x Co y Mn z (OH)2, 0.5 ≤ x ≤ 1, 0 < y ≤ 0.3, 0 < z ≤ 0.3.
[0091] As a possible implementation, the lithium source includes one or more of LiOH, Li2CO3, Li2SO4, LiCl, and LiNO3.
[0092] In some exemplary embodiments, the additive includes one or more of an oxide, hydroxide, chloride, sulfate, and nitrate containing the A element.
[0093] In some embodiments, the sintering treatment includes a first sintering stage and a second sintering stage.
[0094] It should be noted that the "first sintering stage", "second sintering stage" and the like mentioned in the context are only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second" and the like only serve the purpose of non-exhaustive enumeration and description, and should be understood not to constitute a closed limitation on quantity.
[0095] As a possible implementation, the temperature of the first sintering stage is 940°C-970°C; for example, it may be but not limited to 940°C, 950°C, 960°C, 970°C or a range between any two of the above temperatures.
[0096] In some exemplary embodiments, the time of the first sintering stage is 8 hours to 13 hours; for example, it can be but is not limited to 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours or a range between any two of the above times.
[0097] In some optional embodiments, the sintering atmosphere in the first sintering stage includes one or both of oxygen and air.
[0098] As a possible implementation, the temperature of the second sintering stage is 400°C-500°C; for example, it can be but not limited to 400°C, 420°C, 440°C, 460°C, 480°C, 500°C or a range between any two of the above temperatures, etc. The second sintering stage treatment is beneficial to improving the consistency and conductivity of the surface of the matrix particles.
[0099] In some exemplary embodiments, the time of the second sintering stage is 5 hours to 8 hours; for example, it can be but is not limited to 5 hours, 6 hours, 7 hours, 8 hours or a range between any two of the above times.
[0100] One or more embodiments of the present application provide a positive electrode plate, including the coated and modified positive electrode material provided in the present application or the coated and modified positive electrode material prepared by the preparation method provided in the present application.
[0101] One or more embodiments of the present application provide a lithium-ion battery, comprising the above-mentioned positive electrode plate.
[0102] The lithium-ion battery of the present application comprises the above-mentioned coated and modified positive electrode material and has excellent rate performance, cycle stability and thermal stability.
[0103] One or more embodiments of the present application provide an electrical device, including the above-mentioned lithium-ion battery. The electrical device can be an electric car, an electric bicycle, an electric two-wheeled vehicle, an electric car power system, an energy storage system or a mobile storage device, etc., without limitation.
[0104] The electric device of the present application includes the lithium-ion battery provided by the present application, and thus has at least the same advantages as the lithium-ion battery.
[0105] The technical scheme of the present invention is described in detail below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for which specific conditions are not specified in the following embodiments are preferably referred to the guidance given in the present invention, and can also be carried out according to the experimental manual or conventional conditions in the art, or according to the conditions recommended by the manufacturer, or with reference to experimental methods known in the art.
[0106] In the following specific embodiments, the measured parameters of raw material components may have slight deviations within the range of weighing accuracy unless otherwise specified. For temperature and time parameters, acceptable deviations caused by instrument test accuracy or operation accuracy are allowed.
[0107] 1. Preparation of positive electrode materials
[0108] Example 1
[0109] Step S1, weighing the precursor Ni with a molar ratio of nickel ion, cobalt ion and manganese ion of 70:5.2:24.8 0.7 Co 0.052 Mn 0.248 (OH)2 and lithium carbonate, and the molar ratio of lithium element contained in lithium carbonate to the precursor is 1.07. Then, based on the mass of the prepared nickel cobalt manganese oxide lithium material, 1500ppm of ZrO2 powder is weighed, the above three materials are mixed evenly in a high-pressure bag and poured into a high-speed mixer. The rotation speed is maintained at 1500r / min, and after mixing until there are no white spots, it is transferred to a roller kiln for high-temperature sintering. The high-temperature sintering temperature is 950°C, the time is 13h, and the heating rate is 5°C / min; after cooling to room temperature, jaw crushing and air flow crushing are carried out to obtain small-particle single crystal powder with a particle size distribution half-peak width K90 of about 1.1. Subsequently, the small-particle single crystal powder is further placed in a roller kiln for low-temperature sintering. The sintering temperature is 400°C and the time is 5h to obtain a modified matrix material doped with Zr element, with the molecular formula of Li(Ni 0.7 Co 0.052 Mn 0.248 ) 0.9985 Zr 0.0015O2. Step S2, weigh magnesium chloride and aluminum chloride, wherein the molar ratio of the magnesium element contained in the magnesium chloride to the aluminum element contained in the aluminum chloride is 3:1, and the total concentration of the metal salt solution is 2 mol / L. Then weigh a certain amount of sodium carbonate solid alkali and dissolve it in water to prepare an alkaline solution with a concentration of 1.1 mol / L. Subsequently, the salt solution and the alkaline solution are added at a drop rate of 1:1 in a nitrogen environment and a water bath temperature of 120°C for crystal nucleus growth for 24 hours, during which magnetic stirring is continued. After 24 hours, the solution is taken out, centrifuged and dried for 12 hours, and then ground to obtain a powder with the chemical formula [Mg6Al2(CO3)(OH) 16 .4H2O hydrotalcite-like two-dimensional layered materials.
[0110] Step S3, weighing the hydrotalcite-like two-dimensional layered material and the matrix material and performing solid phase grinding for 60 minutes, wherein the mass of the hydrotalcite-like two-dimensional layered material accounts for 0.3% of the mass of the matrix material; then placing the evenly mixed material in a tubular furnace, introducing nitrogen, and calcining at 550°C for 9 hours to obtain a layered bimetallic oxide-coated modified positive electrode material, wherein the chemical formula of the coating layer material is MgAl2O4.
[0111] Example 2
[0112] The preparation method of Example 2 is similar to the preparation method of Example 1, except that in step S3 of Example 2, the mass of the hydrotalcite-like two-dimensional layered material accounts for 0.5% of the mass of the base material, and the rest are the same.
[0113] Example 3
[0114] The preparation method of Example 3 is similar to the preparation method of Example 1, except that in step S3 of Example 3, the mass of the hydrotalcite-like two-dimensional layered material accounts for 1% of the mass of the base material, and the rest are the same.
[0115] Example 4
[0116] The preparation method of Example 4 is similar to the preparation method of Example 1, except that in step S3 of Example 4, the mass of the hydrotalcite-like two-dimensional layered material accounts for 3% of the mass of the base material, and the rest are the same.
[0117] Example 5
[0118] The preparation method of Example 5 is similar to the preparation method of Example 1, except that in step S3 of Example 5, the mass of the hydrotalcite-like two-dimensional layered material accounts for 5% of the mass of the base material, and the rest are the same.
[0119] Example 6
[0120] The preparation method of Example 6 is similar to the preparation method of Example 1, except that in step S3 of Example 6, the mass of the hydrotalcite-like two-dimensional layered material accounts for 0.02% of the mass of the base material, and the rest are the same.
[0121] Example 7
[0122] The preparation method of Example 7 is similar to that of Example 1, except that in step S1 of Example 7, the molar ratio of the main content elements of Ni, Co, and Mn in the matrix precursor is 68.5:9.5:22, the molar ratio of the lithium element contained in the lithium carbonate to the precursor is 1.052, and the doped metal elements are 3000ppm of SrO2, 500ppm of La2O3, and 500ppm of Ga2O3 powder. The high-temperature roasting temperature is 960°C and the time is 12h. The chemical formula of the matrix obtained is Li(Ni 0.685 Co 0.095 Mn 0.22 ) 0.9958 Sr 0.0032 La 0.0003 Ga 0.0007 O2.
[0123] In step S2, nickel nitrate, aluminum nitrate and gallium nitrate salt solution are weighed to obtain [NiAl 1.8 Ga 0.2 (NO3)2(OH)6.4H2O Talc-like two-dimensional layered material. The other steps are the same.
[0124] In step S3, the chemical formula of the bimetallic oxide contained in the coating layer of the positive electrode material is NiAl 1.8 Ga 0.2 O4.
[0125] Example 8
[0126] The preparation method of Example 8 is similar to that of Example 7, except that in step S1 of Example 8, the molar ratio of the main elements Ni, Co, and Mn of the matrix precursor is 60:10:30, the molar ratio of the lithium element contained in the lithium carbonate to the precursor is 1.04, and the doped metal elements are 2500ppm of W2O3 and 500ppm of Al2O3 powder. The high temperature roasting temperature is 940°C and the time is 11h. The chemical formula of the matrix is Li(Ni 0.6 Co 0.1 Mn 0.3 ) 0.9971 W 0.0012 Al 0.0017 O2.
[0127] In step S2, iron chloride and aluminum chloride salt solutions are weighed to obtain [Fe6Al2(CO3)(OH)16 .4H2O hydrotalcite-like two-dimensional layered material. The other steps are the same.
[0128] In step S3, the chemical formula of the bimetallic oxide contained in the coating layer of the positive electrode material is FeAl2O4.
[0129] Example 9
[0130] The preparation method of Example 9 is similar to that of Example 8, except that in step S1 of Example 9, the doped metal elements are 1000 ppm of TiO2 and 500 ppm of LiF powder. The high temperature calcination temperature is 935°C and the time is 11 hours. The chemical formula of the obtained matrix is Li(Ni 0.6 Co 0.1 Mn 0.3 ) 0.9981 Ti 0.0019 O2.
[0131] In step S2, calcium chloride, aluminum chloride and indium chloride salt solutions are weighed to obtain [Ca6Al 1.6 In 0.4 (CO3)(Cl) 16 .4H2O Ca 0.6 In 0.4 Al2O4 hydrotalcite-like two-dimensional layered material. The other steps are the same.
[0132] In step S3, the chemical formula of the bimetallic oxide contained in the coating layer of the positive electrode material is CaAl 1.6 In 0.4 O4. Comparative Example 1
[0133] In Comparative Example 1, the base material is not coated. The specific details of Comparative Example 1 are as follows:
[0134] Step S1, weighing the precursor Ni with a molar ratio of nickel ion, cobalt ion and manganese ion of 70:5.2:24.8 0.7 Co 0.052 Mn 0.248(OH)2 and lithium carbonate, and the molar ratio of lithium element contained in lithium carbonate to the precursor is 1.07. Then, based on the mass of the prepared nickel cobalt manganese oxide material, 1500ppm of ZrO2 powder is weighed, the above three materials are mixed evenly in a high-pressure bag and poured into a high-speed mixer. The rotation speed is maintained at 1500r / min, and after mixing until there are no white spots, it is transferred to a roller kiln for high-temperature sintering. The high-temperature sintering temperature is 950°C, the time is 13h, and the heating rate is 5°C / min; after cooling to room temperature, jaw crushing and air flow crushing are carried out to obtain small-particle single crystal powder with a half-peak width K90 of the particle size distribution of about 1.1. Subsequently, the small-particle single crystal powder is further placed in a roller kiln for low-temperature sintering. The sintering temperature is 400°C and the time is 5h to obtain a modified matrix material doped with Zr element, the chemical formula of which is Li(Ni 0.7 Co 0.052 Mn 0.248 ) 0.9985 Zr 0.0015 O2.
[0135] Step S2: placing the substrate in a tube furnace, introducing nitrogen, and calcining at 550° C. for 9 hours to obtain a positive electrode material.
[0136] Comparative Example 2
[0137] The difference between Comparative Example 2 and Example 1 is that the preparation of step S1 is not performed in Comparative Example 2. The specific details of Comparative Example 2 are as follows:
[0138] Step S1, weigh magnesium chloride and aluminum chloride, wherein the molar ratio of the magnesium element contained in the magnesium chloride to the aluminum element contained in the aluminum chloride is 3:1, and the total concentration of the metal salt solution is 2 mol / L. Then weigh a certain amount of sodium carbonate solid alkali and dissolve it in water to prepare an alkaline solution with a concentration of 1.1 mol / L. Subsequently, the salt solution and the alkaline solution are added at a drop rate of 1:1 in a nitrogen environment and a water bath temperature of 120°C for crystal nucleus growth for 24 hours, during which magnetic stirring is continued. After 24 hours, the solution is taken out, centrifuged and dried for 12 hours, and then ground to obtain a powder with the chemical formula [Mg6Al2(CO3)(OH) 16 .4H2O hydrotalcite-like two-dimensional layered materials.
[0139] Step S2: placing the hydrotalcite-type two-dimensional layered material in a tube furnace, introducing nitrogen, and calcining it at 550° C. for 9 hours to use it as a positive electrode material.
[0140] Comparative Example 3
[0141] The difference between Comparative Example 3 and Example 1 is that in step S3 of Comparative Example 3, the coating material LiAlTiPO4 is used to replace the hydrotalcite-like two-dimensional layered material [Mg6Al2(CO3)(OH) 16.4H2O, step S3 of comparative example 3 is as follows:
[0142] Step S3, weigh the matrix and the coating material LiAlTiPO4 according to a mass ratio of 3:1 and perform solid phase grinding for 60 minutes. Then, place the evenly mixed material in a tubular furnace, introduce nitrogen, and bake at 550°C for 9 hours to obtain a coated modified positive electrode material, wherein the chemical formula of the coating layer material is LiAlTiPO4.
[0143] Comparative Example 4
[0144] The difference between Comparative Example 4 and Example 1 is that in step S3 of Comparative Example 4, only the substrate and the hydrotalcite-like two-dimensional layered material are physically mixed to serve as the positive electrode material. Step S3 of Comparative Example 4 is as follows:
[0145] Step S3, weighing the substrate and the hydrotalcite-like two-dimensional layered material in a mass ratio of 3:1 and performing solid phase grinding for 60 minutes to obtain a positive electrode material.
[0146] The positive electrode material prepared in Example 1 was scanned using a scanning electron microscope, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that the positive electrode material prepared in Example 1 has a coating structure.
[0147] 2. Electrochemical performance test
[0148] The positive electrode material, conductive agent acetylene black, and binder polyvinylidene fluoride prepared in the above embodiments and comparative examples were mixed in a mass ratio of 95:2.5:2.5, and an appropriate amount of N-methylpyrrolidone was added as a dispersant, and ground into a slurry; then the slurry was evenly coated on an aluminum foil, vacuum dried at 120°C for 10 hours, and the dried electrode was rolled with a roller machine, and the aluminum foil was cut with a slicer to cut into a circular electrode with a diameter of 1.2 cm, and the loading amount of the active material was controlled at 12 mg / cm 2 about.
[0149] The liquid battery was assembled in an argon atmosphere glove box, in which a lithium sheet with a diameter of 1.5 cm was used as the negative electrode, a 12 μm PP / PE film was used as the separator, and 10 μL of 1 mol / L LiPF6 electrolyte was added at the interface between the positive electrode sheet, the lithium negative electrode and the electrolyte. The CR2032 button battery was assembled in an environment with a water partial pressure ≤0.1 ppm and an oxygen partial pressure ≤0.1 ppm.
[0150] The assembled button lithium-ion batteries were subjected to rate performance tests, cycle performance tests and metal dissolution tests.
[0151] The cycle performance test method is: 45℃, constant current and constant voltage charging to 4.45V, cut-off current 0.05C, constant current discharge to 2.5V, 0.5CC / 1.0CD, cycle 50 weeks. Voltage range 3.0V-4.5V, vs. Li + / Li. The results are shown in the table.
[0152] EIS performance test method after cycling: The button cell after cycling is subjected to EIS test at 50000 Hz to obtain RSEI and Rct impedance values. The impedance results after cycling of Example 1 and Comparative Example 1 are as follows: Figure 2 As shown by Figure 2 It can be seen that in Example 1, the positive electrode material forms a coating layer, which improves the electronic conductivity of the positive electrode material and reduces the impedance of the positive electrode material.
[0153] The rate performance test method is: test temperature 25℃, constant current and constant voltage charging to 4.45V, cut-off current 0.05C, constant current discharge to 2.5V, test 2CC / 1CD; 2CC / 2CD; 2CC / 4CD; 2CC / 8CD respectively; the results are shown in Table 1.
[0154] Metal dissolution test: The metal content in the electrolyte was tested by ICP at 60°C, charging voltage: 2.5V-4.45V and standing for 14 days. The results are shown in Table 1.
[0155] Table 1
[0156]
[0157] From the comparison of the results of Examples 1-9 and Comparative Examples 1-4, it can be seen that under high current discharge (2CC / 4CD), the rate performance of the positive electrode material with a coating layer in Examples 1-9 is improved by about 0.5%-5% compared with the rate performance of the positive electrode material without coating in Comparative Example 1. At the same time, Examples 1-9 can effectively inhibit the dissolution of powdered metal, especially the dissolution of Mn metal. Compared with Comparative Examples 1-4, Examples 1-9 have better cycle capacity retention and rate performance as a whole, and lower metal dissolution amount; This shows that the two-dimensional layered material [Mn] of hydrotalcite used in this application is more suitable for the production of high-performance liquid electrolytes. 2+ 1-m Q 3+ m (OH)2] q+ (X n- ) q / n .yH2O (0.17≤m≤0.35, 1≤n≤4, 2≤q≤6, 1≤y≤5, M 2+ Ion is Mg 2+ 、Zn 2+ 、Ni 2+ 、Co2+ , Cu 2+ , Ca 2+ , Fe 2+ 、Be 2+ , Ba 2+ , Sr 2+ and Mn 2+ One or more of Q 3+ Ion is A1 3+ Cr 3+ 、Co 3+ , Fe 3+ Sc 3+ , Ga 3+ 、In 3+ and V 3+ One or more of X n- Ion is CO3 2- 、NO3 - 、F - , Cl - Br - ,I - 、CrO4 2 -H2PO4 - PO4 3- 、SO4 2- and SO3 2- The nickel cobalt manganese oxide material is coated with one or more of the following materials, which can effectively stabilize the bulk structure of the nickel cobalt manganese oxide material under lithium intercalation and deintercalation and the interface stability with the electrolyte, reduce side reactions, lattice oxygen precipitation and transition metal dissolution, and improve the cycle stability and rate performance of the material. The structure of the positive electrode material can still maintain a certain stability after high current discharge.
[0158] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0159] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A coated modified positive electrode material, characterized in that: include: A substrate, wherein the substrate comprises a nickel cobalt lithium manganese oxide material, wherein the nickel cobalt lithium manganese oxide material comprises a doping element, and the doping element comprises one or more of Sr, Ga, In, Ta, W, Zr, B, Al, Sb, Mo, Ti, La, Na and Sn; and A coating layer is coated on at least a portion of the surface of the substrate, wherein the coating layer comprises a bimetallic oxide, wherein the bimetallic oxide comprises an M element and a Q element, wherein the M element comprises one or more elements selected from the group consisting of Mg, Zn, Ni, Co, Cu, Ca, Fe, Be, Ba, Sr and Mn, and the Q element comprises one or more elements selected from the group consisting of Al, Cr, Co, Fe, Sc, Ga, In and V.
2. The positive electrode material according to claim 1, characterized in that The positive electrode material has at least one of the following characteristics (1)-(6): (1) The chemical formula of the bimetallic oxide is M m Q q O n , where 1≤m<8, 1≤q<4, 1≤n≤5; (2) The mass of the bimetallic oxide accounts for 0.3%-3% of the mass of the nickel cobalt manganese oxide material; (3) The bimetallic oxide is coated on at least a portion of the surface of the lithium nickel cobalt manganese oxide material; (4) The chemical formula of the lithium nickel cobalt manganese oxide material is Li a Ni x Co y Mn z A b O2, where 1 ≤ a ≤ 1.1, 0.5 ≤ x ≤ 1, 0 < y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z + b = 1, 0 < b ≤ 0.02, and the A element includes one or more of Ga, In, Ta, W, Zr, B, Al, Sb, Mo, Ti, La, Na, Sr, and Sn; (5) The volume average particle size Dv50 of the positive electrode material is 2.5 μm-5.5 μm; (6) The matrix includes single crystal particles and / or polycrystalline particles.
3. A method for preparing a coated modified positive electrode material, characterized in that: The steps include: The positive electrode material is prepared by calcining a mixture containing a matrix and a hydrotalcite-like two-dimensional layered material; wherein the matrix contains a nickel cobalt manganese oxide material, and the nickel cobalt manganese oxide material contains doping elements, and the doping elements include one or more of Sr, Ga, In, Ta, W, Zr, B, Al, Sb, Mo, Ti, La, Na and Sn; the chemical formula of the hydrotalcite-like two-dimensional layered material is [M 2+ 1-m Q 3+ m (OH)2] q+ (X n- ) q / n .yH2O, 0.17≤m≤0.35, 1≤n≤4, 2≤q≤6, 1≤y≤5, M 2+ Ion is Mg 2+ 、Zn 2+ 、Ni 2+ 、Co 2+ , Cu 2+ , Ca 2+ , Fe 2+ 、Be 2+ , Ba 2+ , Sr 2+ and Mn 2+ One or more of Q 3+ Ion is A1 3+ Cr 3+ 、Co 3+ , Fe 3+ Sc 3+ , Ga 3+ 、In 3+ and V 3+ One or more of X n- Ion is CO3 2- 、NO3 - 、F - , Cl - Br - ,I - 、CrO4 2 -H2PO4 - PO4 3- 、SO4 2- and SO3 2- One or more of; The positive electrode material includes a substrate and a coating layer coated on at least a portion of the surface of the substrate, the substrate includes a nickel cobalt manganese oxide material, the coating layer includes a bimetallic oxide, the bimetallic oxide includes an M element and a Q element, the M element includes one or more elements of Mg, Zn, Ni, Co, Cu, Ca, Fe, Be, Ba, Sr and Mn, and the Q element includes one or more elements of Al, Cr, Co, Fe, Sc, Ga, In and V.
4. The preparation method according to claim 3, characterized in that: The mass of the hydrotalcite-like two-dimensional layered material accounts for 0.3%-3% of the mass of the lithium nickel cobalt manganese oxide material contained in the matrix; and / or the calcination temperature is 500°C-800°C, the time is 8h-12h, and the calcination atmosphere includes nitrogen.
5. The preparation method according to claim 3, characterized in that: The preparation method of the hydrotalcite-based two-dimensional layered material comprises: will contain the M 2+ ions and the Q 3+ A mixed salt solution containing the X n- After mixing with the alkaline solution of ions, the crystal nucleus grows to prepare the hydrotalcite-like two-dimensional layered material; Optionally, the nucleation temperature of the crystal nucleus growth is 80°C-120°C; Optionally, the concentration of the alkaline solution is 0.1 mol / L-2 mol / L.
6. The preparation method according to any one of claims 3 to 5, characterized in that: The chemical formula of the lithium nickel cobalt manganese oxide material is Li a Ni x Co y Mn z A b O2, where 1 ≤ a ≤ 1.1, 0.5 ≤ x ≤ 1, 0 < y ≤ 0.3, 0 < z ≤ 0.3, and x + y + z + b = 1, 0 < b ≤ 0.02, and the A element includes one or more of Ga, In, Ta, W, Zr, B, Al, Sb, Mo, Ti, La, Na, Sr, and Sn.
7. The preparation method according to claim 6, characterized in that: The preparation method of the substrate comprises: Mixing a lithium nickel cobalt manganese oxide material precursor, a lithium source and an additive containing the element A, and then performing a sintering treatment; Optionally, the chemical formula of the nickel cobalt lithium manganese oxide material precursor is Ni x Co y Mn z (OH)2, 0.5≤x≤1, 0 <y≤0.3,0<z≤0.3; Optionally, the lithium source includes one or more of LiOH, Li2CO3, Li2SO4, LiCl and LiNO3; Optionally, the additive includes one or more of oxides, hydroxides, chlorides, sulfates and nitrates containing the A element; Optionally, the sintering process includes a first sintering stage and a second sintering stage; Optionally, the sintering temperature of the first sintering stage is 940° C.-970° C., the sintering time is 8 h-13 h, and the sintering atmosphere includes one or both of oxygen and air; Optionally, the sintering temperature of the second sintering stage is 400° C.-500° C., and the sintering time is 5 h-8 h.
8. A positive electrode sheet, characterized in that: A coated and modified positive electrode material comprising the coated and modified positive electrode material as described in any one of claims 1 to 2 or a coated and modified positive electrode material prepared by the preparation method as described in any one of claims 3 to 7.
9. A lithium ion battery, characterized in that: Comprising the positive electrode sheet as described in claim 8.
10. An electrical device, characterized in that: Comprising the lithium ion battery as claimed in claim 9.
Citation Information
Cited By
Battery cell and preparation method therefor and use thereof, and positive electrode material
WO2026157286A1
Positive electrode material, secondary battery and electronic apparatus
WO2026174453A1
